2013
DOI: 10.1155/2013/612848
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Leukocyte Filtration Should Be Avoided during Extracorporeal Circulation

Abstract: Filtration during extracorporeal circulation (ECC) not only removes but also activates leukocytes; therefore, long-term leukocyte filtration may cause adverse effects. In the present study, we tested this hypothesis by priming ECC with 300 mL of canine blood and examining filtration effects in 3 groups (n = 6 each) during 60 min ECC. In the control group (Group C) blood was filtrated with an arterial filter for 60 min; in long-term (Group L) and short-term (Group S) groups, blood was filtrated with a leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Some studies have described leukocyte activation with the use of leukocyte depletion filters,37, 38, 39 but these findings were not consistently replicated in other leukoreduction studies 40, 41, 42, 43. Furthermore, leukocyte rupture is possible with prolonged filtration, resulting in free enzymes and other cellular components 44. Similar to TXB 2 , the increase in PGF 2α concentration after leukoreduction is particularly concerning because PGF 2α is associated with vasoconstriction and bronchoconstriction, which could impact the hemodynamic stability of transfusion recipients 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have described leukocyte activation with the use of leukocyte depletion filters,37, 38, 39 but these findings were not consistently replicated in other leukoreduction studies 40, 41, 42, 43. Furthermore, leukocyte rupture is possible with prolonged filtration, resulting in free enzymes and other cellular components 44. Similar to TXB 2 , the increase in PGF 2α concentration after leukoreduction is particularly concerning because PGF 2α is associated with vasoconstriction and bronchoconstriction, which could impact the hemodynamic stability of transfusion recipients 16…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Furthermore, leukocyte rupture is possible with prolonged filtration, resulting in free enzymes and other cellular components. 44 Similar to TXB 2 , the increase in PGF 2a concentration after leukoreduction is particularly concerning because PGF 2a is associated with vasoconstriction and bronchoconstriction, which could impact the hemodynamic stability of transfusion recipients. 16 The decrease in TXB 2 and PGF 2a concentrations during storage could be associated with the short half-life of these molecules.…”
Section: Eicosanoidmentioning
confidence: 99%
“…16,29 Since leukocyte activation is a crucial step in the induction of inflammatory response 16 and elevated cytokine levels were observed in several LF studies, 6,11,24 it is likely that at least some types of LF activate leukocytes during the filtration process. In a study conducted by Tang et al, 30 leukocyte activation via filtration was supported by elevated plasma norepinephrine (NE) levels 30 and 60 minutes into filtration, as plasma NE is released from activated leukocytes. Thurlow et al also demonstrated that the LG6 filter is not capable of reducing leukocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, prolonged leukocyte filtration, despite continuous reduction of circulating leukocyte count, may increase hemolysis and leukocyte damage, which can induce or exacerbate inflammation and oxidative stress. However, it is difficult to isolate the effects of leukoreduction in ECMO, as they may simply be related to the underlying condition (167).…”
Section: Leukocyte Filtrationmentioning
confidence: 99%